(untitled) (International Conference on Computers in Education, 2020)
The use of alternative assessment to curb the practice of standardized assessment in education in recent years has increased. Educators are challenged with the responsibility to address different needs of diverse learners and the dynamic nature of education that changes alongside rapid technology advancement. Realizing that changes in curriculum instruction and assessments are inevitable, educators attempt to improve their practices in alternative assessment. This includes emphasizing differentiation in assessment. Differentiated assessment makes it possible for educators to collect reliable data of students’ achievement which in turn will be used to plan better strategies in instruction that could address students’ different needs. However, to date, few papers have reported about differentiated assessments that have been carried out, especially in Malaysia. The aim of the present paper is to report on preliminary findings of the impact of PutraPacer as differentiated assessment tool on learning. This pilot study employs a qualitative research method with two undergraduate students and one lecturer as participants. The findings of this pilot study suggest that as a differentiated assessment tool, PutraPacer has supported differentiated learning and assessment among learners in the following ways: (i) reduces pressure in learning, and promotes individualised and self-directed learning experience, (ii) helps assessing students’ understanding, (iii) captures students’ different abilities, and (iv) provides platforms for students to justify responses.